R PENGARUH PENGGUNAAN MEDIA DIGITAL WORDWALL PADA PEMBELAJARAN MATEMATIKA TERHADAP MINAT BELAJAR SISWA KELAS IV SDN 10 SIAK KECIL - Risnawati; Jesi Alexander Alim; Zetra Hainul Putra; Rena (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Student learning interest in mathematics is still low due to the implementation of monotonous learning models resulting in a lack of use of interactive learning media. Therefore, this study aims to determine the effect of the use of digital media wordwalls on student learning interest in mathematics learning in grade IV of SDN 10 Siak Kecil. This study used a pre-experimental design method with a "One group pretest-posttest design" research design. The population of this study was all fourth-grade students of SD Negeri 10 Siak Kecil. The fourth-grade sample served as the experimental class. Based on the analysis results in the discussion that showed low student learning interest with the use of wordwall media, this was proven using the Wilcoxon test obtained an average value of positive rank = 18.00 and negative rank = 0.00. Therefore, Ha is accepted and Ho is rejected. It can be concluded that the use of wordwall media has an effect on student learning interest in mathematics subjects in grade IV of SD Negeri 10 Siak Kecil.